EPIGENETICS TODAY AND TOMORROW - B. F. Vanyushin (Вавиловский журнал генетики и селекции)
Epigenetics is a science of inheritable organism properties that are not associated with changes in the DNA nucleotide sequence but can be indirectly encoded in the genome. The most known epigenetic mechanisms (signals) are enzymatic DNA methylation, the histone code (various enzymatic histone modifications including acetylation, methylation, phosphorylation, ubiquitination and others), and gene silencing mediated by small RNAs (miRNA, siRNA). Very often all these processes are interconnected or even partially interchangeable. This seems to be needed for reliable realization of respective epigenetic signaling. Anyway, these processes are closely associated with chromatin structural and functional organization. DNA methylation in plants and animals carried out by site-specific enzymes cytosine DNA-methyltransferases produces 5-methylcytosine (m5C) residues in such DNA sequences as CG, СNG and СNN. Adenine DNA methylation also occurs in plants. The resulting m5C residues in DNA influence substantially the interaction of DNA with different proteins including regulatory ones. Often DNA methylation prevents DNA binding to such proteins and inhibits gene transcription but sometimes it is a must for binding to other regulatory proteins. Specific m5CрG DNA-binding proteins have been described. Binding of such proteins to DNA orchestrates the whole protein ensemble of the transcription machinery and induces its activity. Thus, DNA methylation can serve as a signal of negative or positive control for gene activities. DNA methylation in eukaryotes is species- and tissue (cell) specific. It is regulated by hormones and aging-related changes, being one of the mechanisms controlling cellular and sex differentiation. DNA methylation controls all genetic functions: DNA replication, recombination, repair, transcription and others. Distortions in DNA methylation and other epigenetic signals cause premature aging, cancer, diabetes, asthma, and severe mental dysfunctions. Changes in the DNA methylation profile accompany carcinogenesis, being a reliable diagnostic marker of various cancer species even at early stages of tumor formation. Epigenetic parameters are very significant for understanding of somaclonal variation mechanisms; characterization of clones and cell cultures, including stem cells at various differentiation stages; and determination of their differentiation directions. Directed change in the DNA methylation profile is an efficient biotechnological tool of activation of transcription of seed storage protein genes in cereals, and it is used, in particular, for inheritable increase in protein content in wheat grain. The inhibitor of DNA methylation 5-azacytidine is used for treatment of skin cancer. Various regulators of enzymatic modifications of histones are efficient in the treatment of different tumors as well. Use of specific small RNAs in the therapy of cancer and other diseases appears to be particularly promising, especially in connection with directed inhibition of transcription of genes responsible for cell malignization and metastasis. The therapeutic action of many known small biologically active peptides seems to be expressed mainly at the epigenetic level. Thus, a phenotype is a product of combined expression of the genome and epigenome. In this regard, the known P. Medawar’s expression «genetics supposes but epigenetics disposes» sounds quite correct and very impressive. In fact, epigenetics is a relatively new, quickly developing, and very promising science of the 21st century that has already engrained in biotechnologies, medicine, and agriculture.